Egr-1 inhibits the expression of extracellular matrix genes in chondrocytes by TNFα-induced MEK/ERK signalling - Rockel, Jason S (BioMed Central, 2009)
INTRODUCTION: TNFα is increased in the synovial fluid of patients with rheumatoid arthritis and osteoarthritis. TNFα activates mitogen-activated kinase kinase (MEK)/extracellular regulated kinase (ERK) in chondrocytes; however, the overall functional relevance of MEK/ERK to TNFα-regulated gene expression in chondrocytes is unknown. METHODS: Chondrocytes were treated with TNFα with or without the MEK1/2 inhibitor U0126 for 24 hours. Microarray analysis and real-time PCR analyses were used to identify genes regulated by TNFα in a MEK1/2-dependent fashion. Promoter/reporter, immunoblot, and electrophoretic mobility shift assays were used to identify transcription factors whose activity in response to TNFα was MEK1/2 dependent. Decoy oligodeoxynucleotides bearing consensus transcription factor binding sites were introduced into chondrocytes to determine the functionality of our results. RESULTS: Approximately 20% of the genes regulated by TNFα in chondrocytes were sensitive to U0126. Transcript regulation of the cartilage-selective matrix genes Col2a1, Agc1 and Hapln1, and of the matrix metalloproteinase genes Mmp-12 and Mmp-9, were U0126 sensitive – whereas regulation of the inflammatory gene macrophage Csf-1 was U0126 insensitive. TNFα-induced regulation of Sox9 and NFκB activity was also U0126 insensitive. Conversely, TNFα-increased early growth response 1 (Egr-1) DNA binding was U0126 sensitive. Transfection of chondrocytes with cognate Egr-1 oligodeoxynucleotides attenuated the ability of TNFα to suppress Col2a1, Agc1 or Hapln1 mRNA expression. CONCLUSIONS: Our results suggest that MEK/ERK and Egr1 are required for TNFα-regulated catabolic and anabolic genes of the cartilage extracellular matrix, and hence may represent potential targets for drug intervention in osteoarthritis or rheumatoid arthritis.